Iman di Balik Layar: Krisis dan Peluang Spiritualitas Remaja Katolik Dalam Fenomena ‘Keuskupan Roblox’ (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of digital technology has significantly transformed the ways in which faith is experienced, particularly in the lives of adolescents. From the perspectives of digital religion and mediatization of religion, digital space is no longer merely a medium, but has become a cultural arena that actively shapes religious practices and meanings. The study aims to analyze these dynamics, especially within the context of Generation Alpha, by examining the opportunities and challenges that emerge in the lived experience of faith in the digital age. The findings indicate that digital environments offer creative, participatory, and contextual opportunities for evangelization, enabling young people to engage actively in constructing their religious experiences. However, this dynamic is inherently ambivalent, as it also risks reducing the meaning of faith to symbolic, instant, and less sacramentally grounded experiences, detached from the communal life of the Church. Furthermore, the formation of religious identity in digital spaces tends to be fluid and performative, potentially leading to superficial relationships and fragmented identities. Therefore, technologically mediated religious experience should be understood as a bridge, rather than a substitute, for authentic faith encounters. The Church is thus called to adopt adaptive and reflective pastoral approaches, positioning media as a means of fostering communio without obscuring the essence of faith. An integrative approach through the synergy of Church, family, and educational institutions is essential to balance digital literacy and spiritual depth, ensuring that adolescent faith continues to grow reflectively and remains rooted in real-life experience.